A plug-in electrophoresis microchip with PCB electrodes for contactless conductivity detection. Issue 5 (9th May 2018) - Yang, Mingpeng; Huang, Zhe; You, Hui
Abstract : A plug-in electrophoresis microchip for large-scale use aimed at improving maintainability with low fabrication and maintenance costs is proposed in this paper. The plug-in microchip improves the maintainability of a device because the damaged microchannel layer can be changed without needing to cut off the circuit wires in the detection component. Obviously, the plug-in structure reduces waste compared with earlier microchips; at present the whole microchip has to be discarded, including the electrode layer and the microchannel layer. The fabrication cost was reduced as far as possible by adopting a steel template and printed circuit board electrodes that avoided the complex photolithography, metal deposition and sputtering processes. The detection performance of our microchip was assessed by electrophoresis experiments. The results showed an acceptable gradient and stable detection performance. The effect of the installation shift between the microchannel layer and the electrode layer brought about by the plug-in structure was also evaluated. The results indicated that, as long as the shift was controlled within a reasonable scope, its effect on the detection performance was acceptable. The plug-in microchip described in this paper represents a new train of thought for the large-scale use and design of portable instruments with electrophoresis microchips in the future.